2023
DOI: 10.1111/cns.14142
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA INPP5F ameliorates stress‐induced hypertension via the miR‐335/Cttn axis in rostral ventrolateral medulla

Abstract: Hypertension is a condition wherein the blood vessel has persistently elevated pressure (defined as blood pressure ≥ 140/90 mmHg). It greatly increases the risk of many other disorders, such as stroke and heart failure. 1,2 The worldwide hypertensive population continues to soar, and more than 1.56 billion adults are expected to have hypertension in 2025. 3 Several factors, such as unhealthy diet, have been linked to hypertension risk. 4 Studies have suggested that chronic exposure to stressors, such as job st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 64 publications
2
7
0
Order By: Relevance
“…The pathogenesis of SIH is closely related to RVLM neuronal hyperexcitation [9,10,29,30]. Our study confirmed that IFN-γ/CCL2 deficiency reduced microglial synaptic engulfment, resulting in increased synaptic density and enhanced neuronal excitability in the RVLM, which is involved in the pathogenesis of SIH.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The pathogenesis of SIH is closely related to RVLM neuronal hyperexcitation [9,10,29,30]. Our study confirmed that IFN-γ/CCL2 deficiency reduced microglial synaptic engulfment, resulting in increased synaptic density and enhanced neuronal excitability in the RVLM, which is involved in the pathogenesis of SIH.…”
Section: Discussionsupporting
confidence: 77%
“…The pathogenesis of SIH is closely related to RVLM neuronal hyperexcitation [9,10,29,30]. Our study confirmed that IFNg/CCL2 deficiency reduced microglial synaptic engulfment, FIGURE 2 Chronic stress induced an increase in the blood pressure, heart rate, renal sympathetic nerve activity, and neuronal activity of rats.…”
Section: Discussionsupporting
confidence: 75%
“…Following the standard rat atlas, the RVLM tissues were extracted by punching coronal sections [ 23 ]. cDNA libraries were generated as previously described [ 24 ]. In brief, TRIzol reagent (Invitrogen, USA) was utilized for the extraction of total RNA from RVLM tissues following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The method of intra-RVLM microinjection has been described in the authors' previous studies [ 22 , 24 ]. In brief, the rats were anaesthetized with isoflurane as described above and placed in prone position, and their heads were fixed in a stereotaxic apparatus (RWD Life Science, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation